Crowdsourcing: Global search and the twisted roles of consumers and producers. (September 2015) - Bauer, Robert M.; Gegenhuber, Thomas
Crowdsourcing spreads and morphs quickly, shaping areas as diverse as creating, organizing, and sharing knowledge; producing digital artifacts; providing services involving tangible assets; or monitoring and evaluating. Crowdsourcing as sourcing by means of 'global search' yields four types of values for sourcing actors: creative expertise, critical items, execution capacity, and bargaining power. It accesses cheap excess capacities at the work realm's margins, channeling them toward production. Provision and utilization of excess capacities rationalize society while intimately connecting to a broader societal trend twisting consumers' and producers' roles: leading toward 'working consumers' and 'consuming producers' and shifting power toward the latter. Similarly, marketers using crowdsourcing's look and feel to camouflage traditional approaches to bringing consumers under control preserve producer power.